Rehabilitacijska vadba hoje po tleh in s tekočim trakom - pregled literature - Pavčič, Janez (Informatica Medica Slovenica, 2014)
Gait rehabilitation after neurological injury typically focuses on task-oriented training with many repetitions of a particular movement. Modern rehabilitation devices, including treadmills, augment gait rehabilitation. However, the question of adequacy of treadmill training in comparison to overground training arises. The article provides an overview of the literature on overground and treadmill walking with an emphasis on their similarities and differences. The focus is on comparing overground and treadmill walking parameters (time and spatial parameters, oxygen consumption, kinematics), benefits of treadmill training after stroke and spinal cord injury, and gait characteristics during overground turning. The overall conclusion is that treadmill training is appropriate for gait rehabilitation.
Keywords: Gait; hoja; rehabilitacija; Rehabilitation; tekoči trak; treadmill